A bovine pericardium rigid prosthesis for left ventricle restoration: 12 years of follow-up - Silveira Filho,Lindemberg Mota (2011)
BACKGROUND: Myocardial infarction might result in dilated left ventricle and numerous techniques have been described to restore the original left ventricle shape and identify tools for late survival assessment. The aim of this study is to compare our experience with a modified Dor procedure using a rigid prosthesis to the septal anterior ventricular exclusion procedure (SAVE) for left ventricle restoration. The EuroScore index for prediction of late follow up survival was evaluated. METHODS: We evaluated 80 patients who underwent left ventricle restoration between 1999 to 2007 and eight patients were excluded with incomplete data. A modified Dor procedure with rigid prosthesis (MD group) was performed on 53 patients and 19 underwent the septal anterior ventricular exclusion procedure (SAVE group). The patients were classified according their left ventricle shape as type I, II or III. Kaplan-Meier and Cox proportional hazard ratio regressions analysis were performed to assess survival after both techniques and expected surgical mortality using EuroScore index ranking after 12 years of follow up. RESULTS: The operative mortality was comparable in both groups ranked by EuroScore index. The groups were comparable for all clinical data, except the MD group had more patients using intra-aortic balloon pumps before surgery, (5.7% vs. 0; P<0.01). Kaplan Meier analysis by left ventricle shape showed comparable survival for all patients, with slightly higher survival for type I. Kaplan Meier analysis of all death showed equivalent survival curves for both techniques after 12 years of follow up (71.5 ± 12.3 vs. 46.6 ±20.5 years; P=0.08). Kaplan Meier analysis of EuroScore index for all patients showed a difference between the three ranked categories, i.e., 0 to 10%, 11 to 49% and higher than 50% expected surgical mortality after 12 years of follow up (70.9 ± 16.2 vs. 67.5 ± 12.7 vs. 53.0 ± 15.5; P=0.003). CONCLUSION: The MD procedure showed consistent ejection fraction improvements after long term follow up. Survival was comparable for all ventricular types and for the MD and SAVE procedures. The EuroScore index is a useful index for late survival assessment of ventricular restoration techniques.